The Effect of Co2+ in the Form of CoCl2 Compounds on α-Amylase Activity - Kusumawati, Perwita Riski; Salirawati, Das (Universitas Negeri Yogyakarta, 2020)
This study aims to determine: (1) the optimum conditions for α-amylase enzyme activity with potato starch as a substrate including incubation time, pH, temperature, substrate concentration, and enzyme concentration, (2) the effect of Co2+ metal ions in the form of CoCl2 compounds on α-amylase enzyme activity with potato starch substrate at optimum conditions. The determination of α-amylase enzyme activity with potato starch substrate was carried out using the dinitrosalicylic acid (DNS) method. The determination of α-amylase enzyme activity with and without the addition of CoCl2 was carried out at the optimum conditions that have been obtained. The variation in the added concentration of CoCl2 were 0.01; 0.02; 0.03; 0.04; and 0.05 M. The data obtained in this study were enzyme activity in units of mg/mL/minute at 37° C. The data analysis used was descriptive qualitative by comparing the activity of the α-amylase enzyme with and without the addition of CoCl2 at optimum conditions. The results of the average α-amylase enzyme activity at optimum conditions (temperature 37° C, pH 7.2, incubation time 15 minutes, substrate concentration 20 mg/mL, and enzyme concentration 40 mg/mL), namely 0.00794 mg/mL at temperature 37° C. For the mean α-amylase enzyme activity with the addition of CoCl2 at a concentration of 0.01; 0.02; 0.03; 0.04; and 0.05 M, respectively 0.0038; 0.0013; 0.0012; 0.0011; and 0.00031 mg/mL per minute at 37° C. Based on these data it can be concluded that the tendency of the Co2+ metal ion is inhibitory and greatly affects the activity of the α-amylase enzyme.